Program “Sang Penyintas” Berjuang Sembuh dari Covid-19 terhadap Gangguan Psikologis Pasien Terkonfirmasi - Andriyanto, Arief; Wicaksono, Arif; Dewi, Catur Prasastia Lukita (Universitas Faletehan, 2024)
Many people who were confirmed to have COVID-19 had to undergo self-isolation, causing sufferers to experience fear, anxiety, and panic because this virus had claimed many lives. The occurred psychological disorders must be addressed immediately through programs in accordance with the problems experienced by confirmed patients who were undergoing quarantine. The purpose of this study was to analyze the program of